2023
DOI: 10.1073/pnas.2302779120
|View full text |Cite
|
Sign up to set email alerts
|

Yeast increases glycolytic flux to support higher growth rates accompanied by decreased metabolite regulation and lower protein phosphorylation

Abstract: Supply of Gibbs free energy and precursors are vital for cellular function and cell metabolism have evolved to be tightly regulated to balance their supply and consumption. Precursors and Gibbs free energy are generated in the central carbon metabolism (CCM), and fluxes through these pathways are precisely regulated. However, how fluxes through CCM pathways are affected by posttranslational modification and allosteric regulation remains poorly understood. Here, we integrated multi-omics data collected under ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Using lower λ values, the model prioritizes minimizing the enzyme usage distribution, aligning more closely with experimental observations. With a λ of 0, the model disregards metabolic fluxes entirely, enabling it to focus on solving for minimal enzyme usage redistribution, only calculating the flux distribution as a function of the former, mirroring what is observed in the cell [ 37 ]. Thus, by being proteome-aware, PARROT is better suited for simulations using pcGEMs than the quadratic and linear implementations of MOMA, given that higher participation of metabolic fluxes lowers the overall predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Using lower λ values, the model prioritizes minimizing the enzyme usage distribution, aligning more closely with experimental observations. With a λ of 0, the model disregards metabolic fluxes entirely, enabling it to focus on solving for minimal enzyme usage redistribution, only calculating the flux distribution as a function of the former, mirroring what is observed in the cell [ 37 ]. Thus, by being proteome-aware, PARROT is better suited for simulations using pcGEMs than the quadratic and linear implementations of MOMA, given that higher participation of metabolic fluxes lowers the overall predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…66,68 Aging cells might face greater energy needs, necessitating adaptive measures for energy balance. Chen et al found that glycolytic flux rises with increased growth rates, 70 suggesting older cells may amplify glycolytic activity to meet energy requirements. Similarly, older cells might have reduced energy efficiency, compensating through heightened glycolytic activity and gene expression.…”
Section: F Variation Of Cellular Age On Gene Expressionmentioning
confidence: 99%
“…Regulation of glycolytic and gluconeogenic activities in the cell is critical to generate energy and direct carbon flux in the face of variable environments and nutrient availability. In bacteria and eukaryotes, allosteric regulation plays an important role, though regulation at the transcriptional and post-transcriptional levels also occurs [1][2][3][4]. However, studies in archaea suggest that allosteric regulation of enzymes involved in central carbon metabolism is less prevalent (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%